Unique characteristics of the tumor immune microenvironment in young patients with metastatic colorectal cancer - Brian D. Griffith; Jenny Lazarus; Jake McGue; Santhoshi Krishnan; Santhoshi Krishnan; Michael I. D’Angelica; Jinru Shia; Irina Dobrosotskaya; Jaiqi Shi; Jacob Edwards; Arvind Rao; Arvind Rao; et al. (Frontiers in Immunology, 2023)
IntroductionMetastatic colorectal cancer (mCRC) remains a common and highly morbid disease, with a recent increase in incidence in patients younger than 50 years. There is an acute need to better understand differences in tumor biology, molecular characteristics, and other age-related differences in the tumor microenvironment (TME).Methods111 patients undergoing curative-intent resection of colorectal liver metastases were stratified by age into those <50 years or >65 years old, and tumors were subjected to multiplex fluorescent immunohistochemistry (mfIHC) to characterize immune infiltration and cellular engagement.ResultsThere was no difference in infiltration or proportion of immune cells based upon age, but the younger cohort had a higher proportion of programmed death-ligand 1 (PD-L1)+ expressing antigen presenting cells (APCs) and demonstrated decreased intercellular distance and increased cellular engagement between tumor cells (TCs) and cytotoxic T lymphocytes (CTLs), and between TCs and APCs. These trends were independent of microsatellite instability in tumors.DiscussionAge-related differences in PD-L1 expression and cellular engagement in the tumor microenvironment of patients with mCRC, findings which were unrelated to microsatellite status, suggest a more active immune microenvironment in younger patients that may offer an opportunity for therapeutic intervention with immune based therapy.